Tinjauan Koreografi Tari Ngayun Nuci Di Semurup Kecamatan Air Hangat Kabupaten Kerinci Provinsi Jambi - Ayu Lestari; Darmawati Darmawati; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2019)
This article aims to describe and explain about the reviews of Dance Choreography Ngayun Nuci in Semurup Sub Regency of Kerinci Hagat Water Jambi province. This type of research is a qualitative descriptive methods. The object of research is the dance Nuci Ngayun. Instrument in this study is the researchers themselves and assisted by mobile phone camera, voice recorder, and stationery. Types of data using primary data and secondary data. Engineering data collection done by the study of librarianship, observation, interviews, and documentation. Technique of data analysis by collecting data, selecting data that is considered important, compiling data that has already been selected, analyzed data with interpretation techniques. The results of this research show that dance Ngayun Nuci is a dance creation which is the development of a tradition of Nuci Ngayun dance serves as the entertainment and aims to preserve traditional arts in Semurup. Dance Dance-shaped Nuci Ngayun group that developed the science of dance composition by koreografernya. Nuci Ngayun dance Creations rendered with planning the choreography for pementasannya. And also this dance movement is fixed at typical dance tradition.